Genetic modifiers of muscular dystrophy act on sarcolemmal resealing and recovery from injury - Quattrocelli, Mattia (PLoS Genet, 2017)
Genetic disruption of the dystrophin complex produces muscular dystrophy characterized by a fragile muscle plasma membrane leading to excessive muscle degeneration. Two genetic modifiers of Duchenne Muscular Dystrophy implicate the transforming growth factor β (TGFβ) pathway, osteopontin encoded by the SPP1 gene and latent TGFβ binding protein 4 (LTBP4). We now evaluated the functional effect of these modifiers in the context of muscle injury and repair to elucidate their mechanisms of action. We found that excess osteopontin exacerbated sarcolemmal injury, and correspondingly, that loss of osteopontin reduced injury extent both in isolated myofibers and in muscle in vivo. We found that ablation of osteopontin was associated with reduced expression of TGFβ and TGFβ-associated pathways. We identified that increased TGFβ resulted in reduced expression of Anxa1 and Anxa6, genes encoding key components of the muscle sarcolemma resealing process. Genetic manipulation of Ltbp4 in dystrophic muscle also directly modulated sarcolemmal resealing, and Ltbp4 alleles acted in concert with Anxa6, a distinct modifier of muscular dystrophy. These data provide a model in which a feed forward loop of TGFβ and osteopontin directly impacts the capacity of muscle to recover from injury, and identifies an intersection of genetic modifiers on muscular dystrophy.